EVALUASI PEMANFAATAN ONLINE PUBLIC ACCESS CATALOG (OPAC) BERBASIS SLIMS MENGGUNAKAN HOT FIT MODEL DI PERPUSTAKAAN UIN PALOPO - Syamsiar Guntur; St. Marwiyah; Salmilah Salmilah (STKIP Pesisir Selatan, 2026)
This study aims to evaluate the utilization of the Senayan Library Management System (SLiMS)-based Online Public Access Catalog (OPAC) at the UIN Palopo Library using the Human–Organization–Technology Fit (HOT-Fit Model) approach. The focus of the study is directed at analyzing the suitability between human, organizational, and technological aspects in supporting the successful implementation of the system and the benefits generated for users and institutions. This study uses a quantitative method with an evaluative survey design. Data collection was carried out by distributing online questionnaires to 100 OPAC user respondents. Data were analyzed using descriptive statistics to describe the level of system utilization for each variable. The results of the study indicate that (1) the utilization of SliMS-based OPAC based on the technological aspect is in the good category with an average value of 3.49, indicating adequate system, information, and service quality, while (2) the human aspect has an average value of 3.50, indicating relatively good system usage and satisfaction, although not yet optimal in the system usability indicator. (3) The organizational aspect is in the good category with an average value of 3.51, but it still requires strengthening socialization and training. (4) The compatibility between human-technology and technology-organization is completely optimal, while human-organization is not optimal.